2013
DOI: 10.1111/mcn.12036
|View full text |Cite
|
Sign up to set email alerts
|

Age‐appropriate infant and young child feeding practices are associated with child nutrition in India: insights from nationally representative data

Abstract: Age-appropriate infant and young child feeding (IYCF) practices are critical to child nutrition. The objective of this paper was to examine the associations between age-appropriate IYCF practices and child nutrition outcomes in India using data from ∼18 463 children of 0-23.9 months old from India's National Family Health Survey, 2005-06-3. The outcome measures were child height-for-age z-score (HAZ), weight-for-age z-score (WAZ), weight-for-height z-score, stunting, underweight and wasting. Linear and logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 30 publications
(67 reference statements)
10
101
1
2
Order By: Relevance
“…Similar findings were reported in India [51] and Malaysia [14]. This was probably due to the widespread breast feeding practices among the respondents who were Malays.…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were reported in India [51] and Malaysia [14]. This was probably due to the widespread breast feeding practices among the respondents who were Malays.…”
Section: Discussionsupporting
confidence: 87%
“…Dietary diversity reduced the incidence of stunting and improved height-for-age scores in a study 58 of more than 18 000 infants in southern India, and similar results are reported for Cambodia, 59 where consumption of animal products was also found to be protective.…”
Section: Nutrition Policies To Promote Healthy Growthsupporting
confidence: 75%
“…Dietary diversity indicators consistently show positive relationships with child LAZ in many contexts (40)(41)(42) . Similar to findings from other studies (18,43,44) , the number of meals and snacks consumed in the previous day was also positively associated with child LAZ.…”
Section: Associations Of Infant and Child Feeding Index With Child Anmentioning
confidence: 97%